2015
DOI: 10.1016/j.yfrne.2015.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Sex differences and rapid estrogen signaling: A look at songbird audition

Abstract: The actions of estrogens have been associated with brain differentiation and sexual dimorphism in a wide range of vertebrates. Here we consider the actions of brain-derived ‘neuroestrogens’ in the forebrain and the accompanying differences and similarities observed between males and females in a variety of species. We summarize recent evidence showing that baseline and fluctuating levels of neuroestrogens within the auditory forebrain of male and female zebra finches are largely similar, and that neuroestrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 164 publications
1
21
0
Order By: Relevance
“…Under physiological conditions in the CNS, aromatase is expressed mainly by neurons (Azcoitia et al, 2011;Jakab et al, 1993;Stanic et al, 2014). Aromatase activity in neurons is regulated by excitatory synaptic transmission (Charlier et al, 2013;Saldanha et al, 2011) and is involved in the regulation of synaptic activity, synaptic plasticity, neurogenesis, pain sensitivity, mood, cognition and reproductive behavior (Cornil et al, 2013;Fester and Rune, 2014;Ghorbanpoor et al, 2014;Krentzel and Remage-Healey, 2015;Saldanha et al, 2011). After brain injury, aromatase expression is induced in reactive astrocytes in rodents (Carswell et al, 2005;Garcia-Segura et al, 1999;Zhang Q et al, 2014), and in reactive astrocytes and radial glia of birds (Duncan et al, 2013a;Peterson et al, 2004Peterson et al, , 2001.…”
Section: Astrocytes As a Source Of Estradiol And Progesteronementioning
confidence: 99%
“…Under physiological conditions in the CNS, aromatase is expressed mainly by neurons (Azcoitia et al, 2011;Jakab et al, 1993;Stanic et al, 2014). Aromatase activity in neurons is regulated by excitatory synaptic transmission (Charlier et al, 2013;Saldanha et al, 2011) and is involved in the regulation of synaptic activity, synaptic plasticity, neurogenesis, pain sensitivity, mood, cognition and reproductive behavior (Cornil et al, 2013;Fester and Rune, 2014;Ghorbanpoor et al, 2014;Krentzel and Remage-Healey, 2015;Saldanha et al, 2011). After brain injury, aromatase expression is induced in reactive astrocytes in rodents (Carswell et al, 2005;Garcia-Segura et al, 1999;Zhang Q et al, 2014), and in reactive astrocytes and radial glia of birds (Duncan et al, 2013a;Peterson et al, 2004Peterson et al, , 2001.…”
Section: Astrocytes As a Source Of Estradiol And Progesteronementioning
confidence: 99%
“…The best known differences are sexual dimorphisms in the size and composition of the song-control nuclei, which regulate song learning and production and are typically larger in males [Nottebohm and Arnold, 1976;Arnold, 1992;Ball and MacdougallShackleton, 2001;Ball, 2016]. However, researchers have also detected effects of sex on gene expression and protein levels in the songbird auditory system as well as on auditory perception [Phillmore et al, 2003;Ikebuchi et al, 2003;Pinaud et al, 2006;Krentzel and Remage-Healey, 2015]. Similar to this study in which we found that monoamines in the auditory forebrain discriminated between song performance in females but not males, many of these studies show female-biased sensitivity to songs or calls.…”
Section: Discussionmentioning
confidence: 99%
“…There are also broad correspondences between egr-1 (also known as ZENK) expression and electrophysiological activity in songbirds: ZENK expression is selective for conspecific social signals (song) over tones only in the presence of estradiol in female white-throated sparrows (Zonotrichia albicolis) (Maney et al, 2006(Maney et al, , 2008Maney and Pinaud, 2011). Estradiol also enhances auditory encoding of song, sometimes through rapid effects of brain-derived estradiol (Krentzel and Remage-Healey, 2015;Remage-Healey, 2012, 2014RemageHealey et al, 2010;Tremere and Pinaud, 2011). In zebra finches, the impact of estradiol extends further to the song control system, as estradiol enhances the neural selectivity for the bird's own song (BOS) but not to conspecific songs and fadrozole injections reduce this selectivity (Remage-Healey and Joshi, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…For example, estradiol shapes auditory tuning in midshipmen fish so that, during the breeding season, females are more sensitive to the harmonics in the calls of courting males, which enhances the adaptive coupling of the sender and the receiver for reproductive success (Sisneros, 2009a,b,c;Sisneros et al, 2004). Similar mechanisms of estradiol-dependent modulation of acoustic communication circuits are present in birds in response to plasma estradiol (Maney et al, 2006(Maney et al, , 2008Maney and Pinaud, 2011;Sanford et al, 2010) and locally produced neuroestrogens (Krentzel and Remage-Healey, 2015;Pawlisch and Remage-Healey, 2015;Remage-Healey, 2012, 2014RemageHealey et al, 2010RemageHealey et al, , 2008Remage-Healey and Joshi, 2012).…”
Section: Introductionmentioning
confidence: 99%